중소제조기업의 수출 비중과 지식탐색 활동 간의 관계 - 김선영(Kim, Sun Young); 박상문(Park, Sangmoon); 정예림(Jung, Ye Lim); 최윤정(Choi, Yun Jeong) (벤처창업연구, 2015)
This study examines the relationships between export intensity and knowledge search activities of Korea SME manufacturers. Using 2,145 firm data from the 2011 SME Technology Statistics Survey, we focused on the nonlinear relationships of export intensity and internal and external knowledge search activities. The results show that there are U-shaped relationships between export intensity and both of internal and external knowledge search activities. Local market-oriented or global market-oriented SMEs than the middle-level of exporters have more search activities both internally and externally. This study extends our understandings on the relationships between export intensity and knowledge search activities. There are some policy implications to develop supporting programs differing in knowledge search activities according to the acceleration of export or globalization of Korean SME manufacturers. 본 연구는 국내 중소제조업에서 수출비중과 지식탐색활동 특성간의 관계를 살펴보고자 한다. 본 연구는 2011년 "중소기업기술통계조사"에 참여한 중소제조업체 2,145개를 대상으로 각 기업의 수출 비중이 조직 내부와 외부 지식탐색활동에 미치는 영향을 실증적으로 분석하였다. 분석 결과, 국내 중소기업의 지식탐색활동은 주요 고객과 시장의 지리적 구성에 따라서 차이가 있었다. 즉, 내수 지향적이거나 수출 지향적 중소기업은 조직 내부 및 외부에 위치한 새로운 지식과 정보를 탐색하고 활용하는데 적극적이었지만, 수출과 내수 시장을 모두 추구하는 기업은 조직 내부 및 외부지식탐색의 수준이 상대적으로 낮았다. 연구의 이론적 시사점은 중소기업이 수출과 지식탐색 및 역량 간의 관계에 대해 새로운 지식을 확장하는 데 이바지한 것이다. 또한, 외부 지식탐색활동 자체도 조직 내부의 특성에 따라 달라질 수 있음을 실증한 것에서도 의의를 찾을 수 있다. 실무적 관점에서는 내수기업에서 수출확대 및 글로벌 중소기업으로 발전에 대해 각 과정의 기업들이 서로 다른 지식탐색활동을 보이고 있다는 점에서 관련 정책 및 지원프로그램의 설계와 운영에도 참조할 수 있다는 것이다.